Farm hygiene - Shirley, Garfield L. (My University, 1905)
Introduction: Hygiene is a science closely related to physiology, which is concerned with the conditions favorable to healthy action of the various parts of the body. Parkes has defined hygiene, "As the art of preserving health". "It aims at rendering growth more perfect, decay less rapid, life more vigorous, and death more remote". The importance of hygienic conditions of the livestock of the farm has not been recognized, as yet only by the veterinary profession and some of our more progressive farmers. There probably are a great many farmers who realize that certain conditions) and cleanliness are necessary, but the real value in dollars and cents of purely sanitary surroundings is appreciated by few. There is that old idea still among some that anything is good enough for animals, and especially is this idea true of swine. In fact, swine are the cleanliest animals on the farm if they have a chance to keep clean. The importance of sanitary conditions for animals may be demonstrated by showing what hygienic conditions have done for the human race. Some of the best dairymen have realized the significance of sanitary conditions, and as a result they receive double the price for their milk. Most farmers will admit that dark hot steaming stables, filled with putrid and irritating gases, are certainly not an adjunct to health. Our greatest hygienic achievements have been accomplished in the army where by aid of the law, certain diseases have practically been eradicated. By introduction of the sanitary reform into the French Army, a saving of 90,000 pounds per annum results in the purchase of horses alone. It does not cost very much more to have things, as they should be than to have them in an unhealthy condition. There are certain guiding principles in sanitary science, which we should understand. If our knowledge is to be based on a scientific foundation, we must understand the examination of air, food, water, soil, etc, act.
Citation: Shirley, Garfield L. Farm hygiene. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Diseases Pracatically Erradicated; Sanitary Science; Impure water's effect on Livestock; Theses